The psychosocial impact of stigma in people with head and neck or lung cancer. Issue 1 (19th September 2011) - Lebel, Sophie; Castonguay, Myriam; Mackness, Gudrun; Irish, Jonathan; Bezjak, Andrea; Devins, Gerald M.
Abstract Background Lung and head and neck cancers are widely believed to produce psychologically destructive stigma because they are linked to avoidable risk‐producing behaviors and are highly visible, but little research has tested these ideas. We examined cancer‐related stigma, its determinants, and its psychosocial impact in lung (n = 107) and head and neck cancer survivors (n = 99) ≤3 years post‐diagnosis. We investigated cancer site, self‐blame, disfigurement, and sex as determinants, benefit finding as a moderator, and illness intrusiveness as a mediator of the relation between stigma and its psychosocial impact. Methods Prospective participants received questionnaire packages 2 weeks before scheduled follow‐up appointments. They self‐administered widely used measures of subjective well‐being, distress, stigma, self‐blame, disfigurement, illness intrusiveness, and post‐traumatic growth. Results As hypothesized, stigma correlated significantly and uniquely with negative psychosocial impact, but contrary to common beliefs, reported stigma was comparatively low. Reported stigma was higher in (i) men than women, (ii) lung as compared with head and neck cancer, and (iii) people who were highly disfigured by cancer and/or its treatment. Benefit finding buffered stigma's deleterious effects, and illness intrusiveness was a partial mediator of its psychosocial impact. Conclusions Stigma exerts a powerful, deleterious psychosocial impact in lung and head and neck cancers, but is less common than believed. Patients should be encouraged to remain involved in valued activities and roles and to use benefit finding to limit its negative effects. Copyright © 2011 John Wiley & Sons, Ltd.